Crises allowed us to do things that were in our government programme. Interview with Ingrida Šimonytė, Prime Minister of Lithuania (2020–2024) - Vilpišauskas , Ramūnas (Politologija, 2025)
Interview conducted by Ramūnas Vilpišauskas on January 16, 2025, in Vilnius. Transcribed by Justė Giedraitytė. Interview was edited for brevity and clarity.